Effects of ozone treatment on the biodegradability of sludge from municipal wastewater treatment plants - Yeom, IT; Lee, KR; Lee, YH; Ahn, KH; Lee, SH (IWA PUBLISHING, 2002)
The effects of ozone pretreatment on the biodegradability of municipal wastewater sludge were determined. Three types of experiments were conducted: anaerobic digestion, aerobic biodegradation, and denitrification using ozone-treated sludge as a carbon source. For 5 days, ozonated sludge at 0.1 gO(3)/g-SS showed about 2-3 times greater biodegradation compared to the raw sludge in both aerobic and anaerobic conditions. In anaerobic experiments, biodegradation increased with ozone dosage up to 0.2 gO(3)/g-SS. Further increase of ozone dosage did not improve the biodegradation. In aerobic condition, about 77% of the ozonated sludge at 0.1 gO(3)/g-SS could be biodegraded after 15 days and is compared with 36% degradation of the untreated sludge. Most of the biodegradation of the ozonated sludge occurred within 5 days while the raw sludge was biodegraded steadily throughout the experimental period. The biodegradation enhancement of ozonated sludge was confirmed in batch denitrification experiments.